Recent Developments in Transition-Metal-Catalyzed Asymmetric Hydrogenation of Enamides - Ponra, Sudipta; Boudet, Bernard; Phansavath, Phannarath; Ratovelomanana-Vidal, Virginie (Synthesis, 2020)
The catalytic asymmetric hydrogenation of prochiral olefins is one of the most widely studied and utilized transformations in asymmetric synthesis. This straightforward, atom economical, inherently direct and sustainable strategy induces chirality in a broad range of substrates and is widely relevant for both industrial applications and academic research. In addition, the asymmetric hydrogenation of enamides has been widely used for the synthesis of chiral amines and their derivatives. In this review, we summarize the recent work in this field, focusing on the development of new catalytic systems and on the extension of these asymmetric reductions to new classes of enamides.1 Introduction2 Asymmetric Hydrogenation of Trisubstituted Enamides2.1 Ruthenium Catalysts2.2 Rhodium Catalysts2.3 Iridium Catalysts2.4 Nickel Catalysts2.5 Cobalt Catalysts3 Asymmetric Hydrogenation of Tetrasubstituted Enamides3.1 Ruthenium Catalysts3.2 Rhodium Catalysts3.3 Nickel Catalysts4 Asymmetric Hydrogenation of Terminal Enamides4.1 Rhodium Catalysts4.2 Cobalt Catalysts5 Rhodium-Catalyzed Asymmetric Hydrogenation of Miscellaneous Enamides6 Conclusions
Keywords: asymmetric hydrogenation; enamides; enantioselectivity; ruthenium; rhodium; iridium; nickel; cobalt